Patterns of healthcare seeking among people reporting chronic conditions in rural sub-Saharan Africa: findings from a population-based study in Burkina Faso - Do, Stefanie; Lohmann, Julia; Brenner, Stephan; Koulidiati, Jean-Louis; Souares-Coutant, Aurélia; Kuunibe, Naasegnibe; Hamadou, Saidou; Hien, Hervé; Winkler, Volker; De Allegri, Manuela (Tropical medicine & international health, 2020)
Objective Non-communicable diseases are rapidly becoming one of the leading causes of morbidity and mortality in sub-Saharan Africa. Yet, little is known about patterns of healthcare seeking among people with chronic conditions in these settings. We aimed to explore determinants of healthcare seeking among people who reported at least one chronic condition in rural Burkina Faso. Methods Data were drawn from a cross-sectional population-based survey conducted across 24 districts on 52 562 individuals from March to June 2017. We used multinomial logistic regression to assess factors associated with seeking care at a formal provider (facility-based care) or at an informal provider (home and traditional treatment) compared to no care. Results 1124 individuals (2% of all respondents) reported at least one chronic condition. Among those, 22.8% reported formal care use, 10.6% informal care use, and 66.6% no care. The presence of other household members reporting a chronic condition (RRR = 0.57, 95%-CI [0.39, 0.82]) was negatively associated with seeking formal care. Wealthier households (RRR = 2.14, 95%-CI [1.26, 3.64]), perceived illness severity (RRR = 3.23, 95%-CI [2.22, 4.70]) and suffering from major chronic conditions (RRR = 1.54, 95%-CI [1.13, 2.11]) were positively associated with seeking formal care. Conclusion Only a minority of individuals with chronic conditions sought formal care, with important differences due to socio-economic status. Policies and interventions aimed at increasing the availability and affordability of services for early detection and management in peripheral settings should be prioritised.